The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1111/j.1464-5491.2011.03246.x
|View full text |Cite
|
Sign up to set email alerts
|

Joint British Diabetes Societies guideline for the management of diabetic ketoacidosis

Abstract: The Joint British Diabetes Societies guidelines for the management of diabetic ketoacidosis (these do not cover Hyperosmolar Hyperglycaemic Syndrome) are available in full at: This article summarizes the main changes from previous guidelines and discusses the rationale for the new recommendations. The key points are: Monitoring of the response to treatment (i) The method of choice for monitoring the response to treatment is bedside measurement of capillary blood ketones using a ketone meter.(ii) If blood keton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
297
0
20

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 281 publications
(335 citation statements)
references
References 48 publications
2
297
0
20
Order By: Relevance
“…37 The diagnosis should not depend upon the presence of ketones in the urine (which may be false negative because of increased resorption or may be present but not associated with ketosis or ketoacidosis) or even blood ketones but should be based on low bicarbonate (<15.0 mmol/L), low pH (<7.3) and quantitative excess of blood ketones over the limit that is considered diagnostic of DKA i.e. 3.0 mmol/L.…”
Section: Recommended Immediate Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…37 The diagnosis should not depend upon the presence of ketones in the urine (which may be false negative because of increased resorption or may be present but not associated with ketosis or ketoacidosis) or even blood ketones but should be based on low bicarbonate (<15.0 mmol/L), low pH (<7.3) and quantitative excess of blood ketones over the limit that is considered diagnostic of DKA i.e. 3.0 mmol/L.…”
Section: Recommended Immediate Actionmentioning
confidence: 99%
“…37 The focus of treatment is to correct pH, bicarbonate and the anion gap. A variable rate intravenous insulin infusion (VRIII) with dextrose and potassium rather than a fixed rate insulin infusion may be needed to avoid hypoglycaemia and hypokalaemia.…”
Section: Further Managementmentioning
confidence: 99%
“…It was at this time that the JBDS Inpatient Care Group was also formed: a collaboration between ABCD, Diabetes UK, and the National Diabetes Inpatient Nurse Group comprising individuals interested in inpatient care. The authors of the initial ABCD DKA guideline were joined by others and a more comprehensive document was written, 1 and revised in 2013. 2 Given the infrequency and heterogeneity of the condition, it remains difficult for any one team to see sufficient numbers of cases to be able to assess the impact of the guidelines.…”
Section: The Diabetes Specialist Teammentioning
confidence: 99%
“…1 By 2013 data presented at the Diabetes UK Annual Professional Conference showed that over 85% of all UK hospitals who responded to an online questionnaire said that they had either adopted or adapted the guideline. In 2013 the guideline was then updated to reflect new evidence and to incorporate some of the suggestions, criticisms and comments made about the first edition.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment protocols were adopted from the Joint British Diabetes Societies in Patient Care Group the Management of Ketoacidosis in Adults (Savage et al 2011) and the Malaysian Clinical Practice Guidelines 2015 (Appendix 1). The study flow diagram was shown in Figure 1 and the DKA monitoring chart was shown in Appendix 2.…”
Section: Treatmentmentioning
confidence: 99%